ANALISIS EFISIENSI PRODUKSI DAN PENDAPATAN USAHATANI PADI SAWAH DI KECAMATAN ABUNG TIMUR KABUPATEN LAMPUNG UTARA - Varingan Prianando Tambunan; Dyah Aring Hepiana Lestari; Fembriarti Erry Prasmatiwi (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aims to determine the level of production efficiency of lowland rice farming and lowland rice farming income. The study was conducted using a survey method. The research was carried out in Sidomukti and Bumi Jaya Villages, with the consideration that both villages had the same type of wetland, namely the largest type of irrigated paddy in 2018. The number of respondents was 75 paddy rice farmers selected using a simple random method. Data collection was carried out in March-April 2019. The amount of income was analyzed by calculating the R/C and the level of production efficiency was analyzed by the stochastic frontier production function. The results showed that lowland rice farming was not yet technically efficient, economically very efficient, and very efficient in price. The income of lowland rice farming in season I to cash costs is IDR9,653,092.11 per ha with an R/C of 2.66 and the income of lowland rice farming to the total cost of IDR5,647,645.87 with an R / C of 1.58 per ha  meaning that farming is profitable to be cultivated. Key words: income, lowland rice farming, production efficiency